Temporal and Contextual Multilevel Perspectives on Procrastination - Kljajic, Kristina (Université d'Ottawa / University of Ottawa, 2023)
Procrastination is a problem for many individuals - especially university students - who may struggle to keep up not only with the requirements of a demanding life domain (i.e., education), but also with the demands of their other life domains (e.g., health, family, finances, and community). Past research on procrastination has mainly focused on understanding why some individuals procrastinate more than others and the consequences of procrastination for those individuals (i.e., between-person level). However, given that almost all individuals procrastinate to a certain extent, there has been an increased interest over the last few years in studying procrastination as a phenomenon that fluctuates within each person, especially over time (i.e., within-person level). Inspired by these burgeoning multilevel perspectives, the purpose of my doctoral thesis was to propose three new multilevel studies to increase our understanding of the antecedents and outcomes of procrastination when comparing university students to one another (i.e., between-person level) and when comparing time points and contexts within each student (i.e., within-person level). In Article 1, I examined the influence of between-person procrastination on the within-person achievement trajectory of students from their last year of high school to their first year at university. A sample of 269 first-year undergraduate students completed a self-reported measure of trait procrastination and their objective grades were obtained at three time points, namely the last year of high school, the first semester at university, and the second semester at university. Using piecewise multilevel growth modeling, the results revealed that students who procrastinated more than their peers tended to have a larger grade decrease from high school to the first semester at university. Although procrastination did not influence the grade change from the first semester to the second semester at university, students who procrastinated more tended to maintain their achievement disadvantage compared to students who procrastinated less. In Article 2, I examined whether procrastination could act as a mediator in the associations between two dimensions of motivation and achievement and affective outcomes both when comparing students to one another (i.e., between-person level) and when comparing the courses taken by each student during a semester to each other (i.e., within-person level). A sample of 359 university students completed self-reported measures of autonomous/controlled motivation, procrastination, and positive/negative affect in each course and their final course grades were obtained at the end of the semester. Using multilevel structural equation modeling, the results showed that procrastination was associated with worse achievement and affective outcomes at both levels of analysis. However, controlled motivation was significantly positively associated with procrastination only at the between-person level, whereas autonomous motivation was significantly negatively associated with procrastination only at the within-person level. This study highlights that, although procrastination tends to generally be detrimental to the success and emotional well-being of students, the motivational antecedent of procrastination differs depending on the level of analysis. In Article 3, I went beyond the academic domain by examining whether procrastination could act as a mediator in the associations between two dimensions of motivation and achievement and affective outcomes both when comparing students to one another (i.e., between-person level) and when comparing the life domains in which each student is invested to each other (i.e., within-person level). A sample of 330 undergraduate students completed self-reported measures of autonomous/controlled motivation, procrastination, self-actual-to-ideal proximity, goal progress, and positive/negative affect in each of their life domains. Using multilevel structural equation modeling, the results showed that autonomous and controlled motivation were associated with less and more procrastination, respectively, and in turn, procrastination was associated with worse achievement and affective outcomes but only at the within-person level. At the between-person level, only controlled motivation was positively related to procrastination, and in turn, procrastination was related to more negative affect and, surprisingly, more goal progress. Overall, all three articles contribute in complementary ways to the idea that proposing new multilevel perspectives can enrich our understanding of procrastination and its associations with antecedents and outcomes. Specifically, the studies in my thesis showed that the multilevel findings sometimes corroborate existing knowledge in the literature (e.g., the negative association between procrastination and academic achievement) and other times offer nuances and unexpected insights in our comprehension of the nomological network related to procrastination (e.g., the motivational antecedents of procrastination and the different relation between procrastination and goal progress depending on the level of analysis).
Keywords: procrastination; motivation; achievement; goal progress; affect; multilevel modeling